Smart Portable Devices Suitable for Cultural Heritage: A Review - Federica Valentini; Andrea Calcaterra; Simonetta Antonaroli; Maurizio Talamo (Sensors, 2018)
This article reviews recent portable sensor technologies to apply in the Cultural Heritage (CH) fields. The review has been prepared in the form of a retrospective description of the sensor’s history and technological evolution, having: new nanomaterials for transducers, miniaturized, portable and integrated sensors, the wireless transmission of the analytical signals, ICT_Information Communication Technology and IoT_Internet of Things to apply to the cultural heritage field. In addition, a new trend of movable tattoo sensors devices is discussed, referred to in situ analysis, which is especially important when scientists are in the presence of un-movable and un-tangible Cultural Heritage and Art Work objects. The new proposed portable contact sensors (directly applied to art work objects and surfaces) are non-invasive and non-destructive to the different materials and surfaces of which cultural heritage is composed.